Using pattern analysis and systematic randomness to allocate U.S. border security resources - Predd, Joel B.; Willis, Henry H.; Setodji, Claude Messan; Stelzner, Chuck; Rand Infrastructure, Safety, and Environment (Organization). Homeland Security; Rand Corporation; United States. Department of Homeland Security Office of Program Analysis and Evaluation (Santa Monica, CA : RAND, 2012)
The U.S. Department of Homeland Security is responsible for protecting U.S. borders against terrorist threats, criminal endeavors, illegal immigration, and contraband. Unfortunately, due to budgetary and other resource constraints, it cannot (3z(Bsee and be(3y (Beverywhere at once. In response, the Office of Border Patrol (OBP) is investigating how pattern and trend analysis and systematic randomness can be used to position border security personnel and equipment in the places and at the times they will be most effective. A RAND study examined how these techniques affect interdiction rates, incorporating results from a RAND-developed agent-based simulation model of the interaction of border patrol agents and illegal smugglers. The model allowed an exploration of how interdiction rates differ across thousands of scenarios that vary by the number of patrols, the rate of illegal flow, the size of the border, and the approach OBP takes to using pattern and trend analysis and systematic randomness. The analysis shows how approaches that combine these two techniques yield higher interdiction rates than approaches using either technique alone, and it identifies circumstances in which combined approaches are competitive with perfect surveillance.s
Introduction -- Resource Allocation, Pattern Analysis, and Systematic Randomness -- Simulation Model of OBP Patrol-Smuggler Interaction -- Findings from the Analysis of the Simulation Model -- Comparison of Border Patrol Stations -- Experimental Design for Evaluating the Contributions of Pattern Analysis and Systematic Randomness -- Conclusions and Recommendations.
"RAND Homeland Security and Defense Center."
Includes bibliographical references (p. 45-46).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Department of Homeland Security -- Planning; Border patrols -- United States; Border security -- United States -- Evaluation; Resource allocation -- United States